ANALISIS PERSAINGAN PERUSAHAAN SEPEDA MOTOR DALAM STRUKTUR PASAR DAN PERILAKU INDUSTRI SEPEDA MOTOR DI INDONESIA TAHUN 2015-2021 - ,Ufira Isbah, Mahendra ,Mardiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Demand for motorcycles in Indonesia as a practical means of transportation will continue to grow and increase from 2015 to 2021. The increased demand will create competition between manufacturers of the motorcycle industry in Indonesia with various technological innovations in accordance with the wishes of the public. and society. continue to provide benefits for industry players. The purpose of this research is to analyze competition between motorcycle companies in the market structure and behavior of the motorcycle industry in Indonesia. The main data source in this study uses secondary data from the Indonesian Motorcycle Industry Association (AISI). The analytical method in this study uses the Structure-Conduct-Performance (SCP) analysis method with concentration ratio analysis (CR), calculation of IHH (Hirscham-Herfiendahl index), market share and Gini index (Gini coefficient) to analyze market structure. and the behavior of the motorcycle industry in Indonesia. The results of calculating the CR4 value, which means that market control is concentrated in Honda, Yamaha, Suzuki and Kawasaki companies, results in a tight oligopoly motorcycle industry market structure. the motorcycle industry in Indonesia is found in the Dominant Company market criteria. and In practice it tends to be monopolistic. Based on the research results, the calculation of sales distribution is calculated using the Gini Coefficient (Gini Index) for the motorcycle industry in Indonesia where there is an increase in the Gini Coefficient Value, this indicates that the value of sales distribution inequality is high. which according to sales distribution is still uneven. Keywords: Structure, Behavior, Motorcycle.